2021
DOI: 10.5222/terh.2021.47640
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Dysnatremia in COVID-19 Disease

Abstract: Objective: The infection of Corona 2019 (COVID-19) had first diagnosed in December 2019 and evolved into a worldwide pandemic in March 2020. In Turkey first diagnose was announced in March 2020. Low costed and easily accessible laboratory parameters needed for predicting the prognosis of this disease as its outcome pattern vary greatly from patient to patient. There is promising data on predicting the outcomes with disnatremic results. Methods: In this study we retrospectively investigated all adults with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In accordance with some previous studies, 7,10,11,13 signi cantly increased number of non-survivors amongst hypernatremic COVID-19 positive participants (44/106) compared to that of hyponatremic (10/47) and eunatremic (19/238) participants suggested that outcome of hypernatremia is harsher than the hyponatremia. The total physiological alterations resulting from hypernatremia leading to negative inotropic effect, increased hyperventilation, altered glucose metabolism, brain cell shrinkage and vascular rupture may be the contributory factor of high mortality in hypernatremia.…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…In accordance with some previous studies, 7,10,11,13 signi cantly increased number of non-survivors amongst hypernatremic COVID-19 positive participants (44/106) compared to that of hyponatremic (10/47) and eunatremic (19/238) participants suggested that outcome of hypernatremia is harsher than the hyponatremia. The total physiological alterations resulting from hypernatremia leading to negative inotropic effect, increased hyperventilation, altered glucose metabolism, brain cell shrinkage and vascular rupture may be the contributory factor of high mortality in hypernatremia.…”
Section: Methodssupporting
confidence: 91%
“…32 We employed both the severity scores but due to non-availability of all the required parameters we could calculate the SOFA score of only 28 positive patients, associated with severe illness and increased fatality rate. [4][5][6][7][8][9]13,20,33 Comparable to our ndings, few studies have also been reported testifying hypernatremia to be a common extra-pulmonary impediment in COVID-19 patients associated with adverse outcome, increased length of ICU stay and even increase mortality. 1,10,34 Angiotensin-converting enzyme 2 (ACE2), a counter regulator of reninangiotensin-aldosterone system (RAAS), is considered as the speci c functional receptor for invasion of the SARS-CoV-2 into the human body leading to suboptimal level of this enzyme in infected individuals.…”
Section: Methodsmentioning
confidence: 54%
See 2 more Smart Citations